Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/bse.3159
|View full text |Cite
|
Sign up to set email alerts
|

How do environmental regulations influence resource misallocation in China? The role of investment flows

Abstract: In recent years, the Chinese government has implemented numerous regulations to address environmental deterioration. Several studies have examined the effect of environmental regulation policies on China's economic performance. However, whether environmental regulations can alleviate China's resource misallocation problem—a critical issue in transitional economies—remains unclear. This study fills this gap in the literature by employing the difference‐in‐differences method to examine how environmental regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…They found that environmental regulation policies can effectively promote enterprise R&D activities and improve energy e ciency (Mandal's 2010; Lanoie et al 2011;. At the same time, environmental regulations could stimulate enterprises with a high degree of environmental protection to enter the market, and force high-polluting and high-emission enterprises to exit the market (Du et al 2020;Li et al 2021). Because, the introduction of environmental regulations would signi cantly increase the entry cost and the capacity adjustment cost (Ryan 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that environmental regulation policies can effectively promote enterprise R&D activities and improve energy e ciency (Mandal's 2010; Lanoie et al 2011;. At the same time, environmental regulations could stimulate enterprises with a high degree of environmental protection to enter the market, and force high-polluting and high-emission enterprises to exit the market (Du et al 2020;Li et al 2021). Because, the introduction of environmental regulations would signi cantly increase the entry cost and the capacity adjustment cost (Ryan 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that environmental regulation policies can effectively promote enterprise R&D activities and improve energy efficiency (Mandal's 2010;Lanoie et al 2011;Li et al 2020). At the same time, environmental regulations could stimulate enterprises with a high degree of environmental protection to enter the market, and force high-polluting and high-emission enterprises to exit the market (Du et al 2020;Li et al 2021). Because, the introduction of environmental regulations would significantly increase the entry cost and the capacity adjustment cost (Ryan 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are mainly two ways that can cause an increase in regional inequality in China. First, there is a city-level resource misallocation in China [7]. All the best resources are found in first-tier cities, and all the citizens in the city are the biggest beneficiary by receiving considerable welfare.…”
Section: Literature Reviewmentioning
confidence: 99%